KNOWLEDGE, ATTITUDE AND PRACTICE OF KANGAROO MOTHER CARE AMONG POSTNATAL MOTHERS IN A TERTIARY CARE CENTRE OF HARARI REGION, HARAR, ETHIOPIA - Jamie, Arif Hussen (YCAB Publisher & IAKMI SULTRA, 2020)
Background: Kangaroo Mother Care (KMC) is a method was invented by Dr. Rey in 1978 and developed by Dr. Martinez and Dr. Navarrete until 1994. It is holding a small nappy neonate in skin to skin contact, prone and upright on the maternal chest. At first it was developed to alleviate overcrowding, and insufficient resources in neonatal intensive care units. But today it is formally approved by WHO.Objective: The aim of this study was to assess knowledge, attitude and practice of Kangaroo mother care among postnatal mothers in a tertiary care center of Harari region, Harar, Ethiopia, 2020.Method: An institution based cross-sectional study method was conducted in Hiwot-Fana Specialized Referral Hospital in Harar town. Sample size was calculated by using single population proportion sample formula and the final sample size was 166. The study subject was selected by using consecutive sampling method, and adopted data collection tool was used. Data were analyzed using SPSS version 20. Descriptive analyses were performed and bivariate analyses were used to find out the association of independent variables.Results: There was 82.53% of mothers had good knowledge, 82.53% had positive attitude towards KMC, 32.12% practiced KMC correctly. The participants also reported the benefits of KMC, such as protection from infection, warmth to the baby, exclusive breast feeding, weight gain and growth, early discharge from hospital, safety and love.Conclusion: The finding of this study showed that there was a clear gap in knowledge and practice. Therefore, it is very important to have health education sessions during ANC follow-up on KMC. A qualitative research to explore temporal relationship is also recommended.